Mengenal Backend Developer : Skill, dan Tanggung Jawab Menjadi Backend Developer - Benaya Chessa Sarmanela; Alya Nur Samiya; Margaretha Evi Yuliana (Prosiding Seminar Nasional Teknologi Informasi dan Bisnis, 2023)
This article explains the role and responsibilities of a Backend Developer in web development. A Backend Developer is responsible for database development, scripting, and website architecture. They focus on the functions and systems that are not visible to end users. The article also describes some basic tasks that a Backend Developer has, such as creating and managing databases, using server-side programming languages, developing Content Management Systems (CMS), and integrating APIs